1986
DOI: 10.1159/000457083
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Plasma-Free Thyroxine and Triiodothyronine Concentrations during the Perinatal Period and Maternofetal Transfer of Thyroid Hormones in the Rabbit

Abstract: Although rabbit has been used as a convenient animal model in understanding the role of thyroid hormones during the perinatal development, ontogenetic changes in plasma-free thyroxine or triiodothyronine concentration has not been studied in this species. We delineated the ontogeny of immunoreactive plasma-free thyroxine and triiodothyronine concentration during the perinatal period. It is generally believed that thyroid hormones do not cross the placenta from the mother to the fetus in sufficient concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…The dose that we used caused a signifi cant improvement in static pressure-volume curves of the preterm rabbit lungs [7]. In similarly treated preterm rabbits we found cord blood elevations in fetal T3 to over 500 ng/dl [19], values comparable to those re ported by others [6,7], The effects of mater nal T3 administration may not cause a pure T3 effect on the fetal lung because the moth ers become thyrotoxic and the fetuses be come hyperglycemic [7,19], While precursor incorporation into surfactant was found to be supraadditive in vitro [21,22], T3 antago nized the increased fatty acid synthesis and glycogenolysis noted with corticosteroids [11], Devaskar et al [7] found that T3 pre vented the runting seen with maternal corti costeroid treatment but did not cause an increased deflation stability above that seen with corticosteroid alone. They also noted increased death after delivery in sponta neously breathing newborns relative to ani mals that received corticosteroids alone [7], Our previous results indicated that T3 improved dynamic compliance very little, and the effect of surfactant on T3-treated fetal lungs was less striking than the effect of surfactant on corticosteroid-treated lungs [19].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The dose that we used caused a signifi cant improvement in static pressure-volume curves of the preterm rabbit lungs [7]. In similarly treated preterm rabbits we found cord blood elevations in fetal T3 to over 500 ng/dl [19], values comparable to those re ported by others [6,7], The effects of mater nal T3 administration may not cause a pure T3 effect on the fetal lung because the moth ers become thyrotoxic and the fetuses be come hyperglycemic [7,19], While precursor incorporation into surfactant was found to be supraadditive in vitro [21,22], T3 antago nized the increased fatty acid synthesis and glycogenolysis noted with corticosteroids [11], Devaskar et al [7] found that T3 pre vented the runting seen with maternal corti costeroid treatment but did not cause an increased deflation stability above that seen with corticosteroid alone. They also noted increased death after delivery in sponta neously breathing newborns relative to ani mals that received corticosteroids alone [7], Our previous results indicated that T3 improved dynamic compliance very little, and the effect of surfactant on T3-treated fetal lungs was less striking than the effect of surfactant on corticosteroid-treated lungs [19].…”
Section: Discussionsupporting
confidence: 82%
“…The dose of T3 was chosen based on the reports of Devaskar et al [6] demonstrating placen tal transfer in the rabbit of high doses of T3 given to the mother, a result similar to that reported by Gross et al [5] in the pregnant rat. The dose that we used caused a signifi cant improvement in static pressure-volume curves of the preterm rabbit lungs [7].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the developmental changes of reverse T3 separate from active T3 have not been delineated in the rabbit, recent studies reveal the neonatal serum total T3 concentrations to be similar to the fetal levels till day 4 of life. An increase in total T3 is observed starting day 4 and reaching a peak on day 7 of life [27]. Serum T3 concentrations in the rat neonate do not correlate with the brain T3 concentrations, the former being dependent on production and clearance of T3 [28].…”
Section: Discussionmentioning
confidence: 89%